Case report: Multi-organ injuries induced by tislelizumab - Yuan, Man; Han, Ning; Shu, Li; Yan, Libo; Tang, Hong (Frontiers in Immunology, 2025)
The use of immune checkpoint inhibitors (ICIs) often develops immune-related adverse events (irAEs). However, irAEs-induced multi-organ injuries remain a rare event. We herein report a case of multi-organ injuries induced by tislelizumab in a lung squamous cell carcinoma (LUSC) patient. A 68-year-old man had undergone neoadjuvant chemotherapy with paclitaxel, carboplatin, and tislelizumab. He presented with a 1-month history of nausea and poor appetite after the second dose of therapy. During investigations, rhabdomyolysis, liver, kidney, and thyroid damage were detected. After multi-disciplinary consultation, multi-organ injuries related to ICIs (striated muscle, liver, kidney, and thyroid) were considered to result from cumulated irAEs induced by tislelizumab. The patient was treated with levothyroxine, methylprednisolone, intravenous immunoglobulins, and continuous renal replacement therapy. After treatment, the patient recovered and was discharged from the hospital. The patient presented with multiple organ damage, not single immunity treatment adverse reactions, relatively rare. In clinical work, irAEs are likely not a single-system organ disorder and many kinds of attention need to be combined with the risk of multi-system damage.